Implementasi WhatsApp API Untuk Sistem Inventory Produk Jadi Pada PT. Cita Pangan Nusantara Berkah - Azhari (CV. Multi Kreasi Media, 2023)
WhatsApp API is a service from WhatsApp that allows you to connect with other software that can carry out two-way communication. Inventory is a resource that is provided either for production materials or finished products that are provided to meet consumer demand. Meanwhile, finished products are goods that have been processed from raw materials into ready-to-use goods. Currently the inventory system of PT. Cita Pangan Nusantara Berkah is still processing data on the finished product after production using excel and manual software, but the process is still not running optimally and is less efficient in disseminating finished product data quickly so that sometimes the service between management and service to customers is less than optimal. However, with the results of this study, a web application that utilizes the WhatsApp API is able to disseminate data on the finished product faster than usual.